Characterization of Maize Phytochrome-Interacting Factors in Light Signaling and Photomorphogenesis. Issue 2 (26th July 2019) - Wu, Guangxia; Zhao, Yongping; Shen, Rongxin; Wang, Baobao; Xie, Yurong; Ma, Xiaojing; Zheng, Zhigang; Wang, Haiyang
Abstract : Phytochrome-interacting factors regulate light signaling and photomorphogenesis in maize. Abstract: Increasing planting density has been an effective means of increasing maize ( Zea mays ssp. mays ) yield per unit of land area over the past few decades. However, high-density planting will cause a reduction in the ratio of red to far-red incident light, which could trigger the shade avoidance syndrome and reduce yield. The molecular mechanisms regulating the shade avoidance syndrome are well established in Arabidopsis ( Arabidopsis thaliana ) but poorly understood in maize. Here, we conducted an initial functional characterization of the maize Phytochrome-Interacting Factor ( PIF ) gene family in regulating light signaling and photomorphogenesis. The maize genome contains seven distinct PIF genes, which could be grouped into three subfamilies: ZmPIF3s, ZmPIF4s, and ZmPIF5s . Similar to the Arabidopsis PIFs, all ZmPIF proteins are exclusively localized to the nucleus and most of them can form nuclear bodies upon light irradiation. We show that all of the ZmPIF proteins could interact with ZmphyB. Heterologous expression of each ZmPIF member could partially or fully rescue the phenotype of the Arabidopsis pifq mutant, and some of these proteins conferred enhanced shade avoidance syndrome in Arabidopsis. Interestingly, all ZmPIF proteins expressed in Arabidopsis are much more stable than their Arabidopsis counterparts upon exposure to red light. Moreover, the Zmpif3, Zmpif4, and Zmpif5 knockout mutants generated via CRISPR/Cas9 technology all showed severely suppressed mesocotyl elongation in dark-grown seedlings and were less responsive to simulated shade treatment. Taken together, our results reveal both conserved and distinct molecular properties of ZmPIFs in regulating light signaling and photomorphogenesis in maize.